2021
DOI: 10.1002/adfm.202010048
|View full text |Cite
|
Sign up to set email alerts
|

Polydiketopyrrolopyrroles Carrying Ethylene Glycol Substituents as Efficient Mixed Ion‐Electron Conductors for Biocompatible Organic Electrochemical Transistors

Abstract: A comprehensive investigation of four polydiketopyrrolopyrroles (PDPPs) with increasing ethylene glycol (EG) content and varying nature of comonomer is presented, and guidelines for the design of efficient mixed ion‐electron conductors (MIECs) are deduced. The studies in NaCl electrolyte‐gated organic electrochemical transistors (OECTs) reveal that a high amount of EG on the DPP moiety is essential for MIEC. The PDPP containing 52 wt% EG exhibits a high volumetric capacitance of 338 F cm−3 (at 0.8 V), a high h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 38 publications
2
59
0
Order By: Relevance
“…Several molecular design strategies have been pursued to maximise the OECT performance of EG functionalised conjugated polymers. 23,27,28 Broadly speaking these synthetic modifications can be categorised into conjugated polymer backbone engineering 22,[29][30][31][32][33] and EG-side chain engineering. 25,[34][35][36][37][38][39] In this context, one of the highest-performing EG-functionalised polymers reported up to date is poly(2-(3,3-bis(2-(2-(2-methoxyethoxy) ethoxy)ethoxy)-[2,2 0 -bithiophen]-5-yl)thieno[3,2-b]thiophene), p(g2T-TT).…”
Section: Materials Horizonsmentioning
confidence: 99%
“…Several molecular design strategies have been pursued to maximise the OECT performance of EG functionalised conjugated polymers. 23,27,28 Broadly speaking these synthetic modifications can be categorised into conjugated polymer backbone engineering 22,[29][30][31][32][33] and EG-side chain engineering. 25,[34][35][36][37][38][39] In this context, one of the highest-performing EG-functionalised polymers reported up to date is poly(2-(3,3-bis(2-(2-(2-methoxyethoxy) ethoxy)ethoxy)-[2,2 0 -bithiophen]-5-yl)thieno[3,2-b]thiophene), p(g2T-TT).…”
Section: Materials Horizonsmentioning
confidence: 99%
“…In addition, other DPP-based polymers with different donors and side chains are studied. 66,67 Because it is difficult to lower the LUMO energy levels to achieve electron transport and maintain air stability, high-performance n-type conjugated polymers are very rare. Moreover, the existence of electrolyte (most commonly NaCl solution) aggravates the instability of polymers and makes the development of n-type OECTs F I G U R E 6 Chemical structures of the p-type third-generation semiconducting polymers for OECTs.…”
Section: The Third-generation Semiconducting Polymers For Oectsmentioning
confidence: 99%
“…65 (E) DPP-based polymers. 36,39,66,67 DPP, diketopyrrolopyrrolep; IID, Isoindigo; OECTs, organic electrochemical transistors; PyDPP, pyridine-flanked DPP troublesome. The lack of n-type polymers whose performances can be comparable to p-type restricts the development of complementary logic circuits, which are the basis of flexible electronics.…”
Section: The Third-generation Semiconducting Polymers For Oectsmentioning
confidence: 99%
“…McCulloch et al have recently reported three donor-acceptor (D-A) type glycolated TDPPs and highlighted the relationship between the polaron delocalization and the OECT mobility. One of these DPP polymers had a high mC* of about 300 F cm À1 V À1 s À1 but a high threshold voltage of 0.52 V. [37][38][39][40][41] Thienylenevinylene (TVT) and thiophene-benzothiadiazole-thiophene (TBTT) are two popular electron-donating units used to form D-A type polymers with high charge-carrier mobilities in OFETs. [42][43][44] Incorporating the highly p-extended TVT and TBTT units in the main chain with DPP promotes intermolecular p-p stacking.…”
Section: Introductionmentioning
confidence: 99%